Emotional Intelligence as A Predictor of Academic Stress Management among Undergraduate Students - Abdulmutalib Opeyemi Adio; Adekola Kamil Lasisi (Universitas Pendidikan Indonesia (UPI), 2023)
The study investigates emotional intelligence as a predictor of academic stress management among undergraduate students. A descriptive research design was used. Two purposes and two research hypotheses guided the study. The target population was all the undergraduate students in the Faculty of Education. Purposive sampling was used to select two Departments and 100 participants were selected using purposive and simple random sampling techniques. Two different instruments were adapted for data collection titled Emotional Intelligence Scale (EIS) and Student Academic Stress Scale (SASS). A pilot study of 25 undergraduate students was used to test-retest within three weeks intervals to test its reliability. The Cronbach's Alpha for Internal Consistency Reliability was 0.78 and 0.85, respectively. Data collected were analyzed using percentages, Pearson’s Product Moment Correlation Statistics (PPMS), and a t-test statistical tool to test null hypotheses at a 0.05 level of significance were used. The study discovers that there is a significant gender difference in academic stress management between male and female undergraduate students at Al-Hikmah University, Ilorin-Nigeria. The result shows that there was a significant relationship between emotional intelligence and academic stress management among undergraduate students at Al-Hikmah University, Ilorin-Nigeria. The study concludes that emotional intelligence has a significant relationship with academic stress management among postgraduate students at Al-Hikmah University, Ilorin-Nigeria.